Electrospun core-shell structured nanofilm as a novel colon-specific delivery system for protein. (1st August 2017) - Wen, Peng; Feng, Kun; Yang, Huan; Huang, Xiao; Zong, Min-Hua; Lou, Wen-Yong; Li, Ning; Wu, Hong
Graphical abstract: The core-shell structured electrospun nanofilm is a promising colon-specific delivery system for bioactive protein. Highlights: The core-shell structured nanofilm was fabricated by coaxial electrospinning. The nanofilm exhibited a good colon-specific and controlled release property. The release of BSA from nanofilm in SCF was dominant by erosion mechanism. Abstract: A novel core-shell structured nanofilm for the delivery of protein to the colon was developed by coaxial electrospinning using bovine serum albumin (BSA) as protein model. Firstly, the BSA-loaded chitosan nanoparticle was prepared by ionic gelation, and then the coaxial nanofilm was fabricated using alginate as shell layer and the BSA-loaded chitosan nanoparticle as core layer. Scanning electron microscopy analysis showed that the obtained nanofilm exhibited a smooth surface, and the core-shell structure was evidenced by the aid of transmission electron microscopy. There was little change in the secondary structure of encapsulated BSA and around 75% of BSA was released in the simulated colonic fluid. The corresponding kinetics models of BSA release in different simulated digestive fluids were built and the results revealed that the release of BSA in colon followed a complex mechanism. This study shows that electrospun nanofilm is a promising colon-specific delivery system for bioactive protein.